Papillary Cystadenoma: An Incidental Finding in Tubal Ligation - Tabitha Lynn Ward; Neda Zarrin-Khameh (Case Reports in Obstetrics and Gynecology)
von Hippel-Lindau disease (vHLD) is a rare autosomal dominant disorder with multiple benign and malignant tumors of different organs. We report a papillary cystadenoma of the mesosalpinx found in close association with an adenomatoid tumor discovered incidentally following tubal ligation in a patient with vHLD.